Regional expansion of the beef industry in Brazil: from the coast to the Amazon, 1966–2017. Issue 1 (31st December 2022) - Vale, Ricardo; Vale, Petterson; Gibbs, Holly; Pedrón, Daniel; Engelmann, Jens; Pereira, Ritaumaria; Barreto, Paulo
ABSTRACT: A regional approach to the study of Brazil's beef industry is increasingly relevant as deforestation takes centre stage in policy debates worldwide. To what extent has beef production expanded toward regions hosting sensitive ecosystems such as the Amazon? Important data limitations remain to answer this question, especially regarding slaughterhouses, fundamental to the beef supply chain. This paper addresses the data gap on slaughterhouse location and history and provides novel regional analysis. We map the beef industry's evolution into Brazil's interior over the last six decades and quantify changes in market concentration between 2006 and 2016. To accomplish this, we triangulated across fiscal and animal sanitation data sources to produce the first longitudinal dataset with information on the opening and closing dates, locations, and production volumes of 2602 slaughterhouses. We show the linear movement of slaughterhouses and cattle herds to the Amazon by tracking their geographical centres of gravity. We also show the clustering pattern of slaughterhouses. Until the 1960s, all the geographical clusters were located south of the capital, Brasília. By the early 2000s, clusters north of Brasília were almost as extensive. Finally, we assessed the degree of market power that the largest beef-processing companies possess. The results indicate that market concentration increased in regions of more recent settlement further away from the coast, and that it remained relatively stable in states near the coast (Minas Gerais, São Paulo). The results shed light on the relationship between displacement toward the Amazon and Cerrado regions and economic concentration.